2021
DOI: 10.1183/16000617.0230-2020
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of residential radon and lung cancer in never-smokers

Abstract: BackgroundGlobally, radon is the leading risk factor for lung cancer in never-smokers (LCINS). In this study, we systematically reviewed and meta-analysed the evidence of the risk of LCINS associated with residential radon exposure.MethodsMedline and Embase databases were searched using predefined inclusion and exclusion criteria to identify relevant studies published from 1 January 1990 to 5 March 2020 focused on never-smokers. We identified four pooled collaborative studies (incorporating data from 24 case–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 74 publications
3
36
0
5
Order By: Relevance
“…One of the serious carcinogens is naturally occurring radon, which is considered as a second lung cancer risk factor after smoking. The large analysis of the studies conducted in never-smokers confirmed the relationship between residual radon and lung cancer, which was higher in never than in ever smokers and among man than women [49]. However, the synergistic effect of radon with smoking was pointed in this review leading to the conclusion, that, for both sexes, people living in the radon-prone area (> 100 Bq/m 3 ) should be considered as a high-risk group.…”
Section: Environmental Factorsmentioning
confidence: 68%
“…One of the serious carcinogens is naturally occurring radon, which is considered as a second lung cancer risk factor after smoking. The large analysis of the studies conducted in never-smokers confirmed the relationship between residual radon and lung cancer, which was higher in never than in ever smokers and among man than women [49]. However, the synergistic effect of radon with smoking was pointed in this review leading to the conclusion, that, for both sexes, people living in the radon-prone area (> 100 Bq/m 3 ) should be considered as a high-risk group.…”
Section: Environmental Factorsmentioning
confidence: 68%
“…Radon exposure has been considered a risk factor for SCLC. Torres-Durán et al 20 and others 40 , 41 , 42 reported higher levels of residential radon exposure among never-smoker patients with SCLC. However, the causal relationship between radon and SCLC remains to be determined.…”
Section: Discussionmentioning
confidence: 88%
“…Radon-attributable lung cancer deaths for all 66 countries totaled 226,057 in 2012 and represented a median of 3.0% of total cancer deaths [77]. Recently, multiple published studies have measured the risk of developing lung cancer following residential or occupational radon exposure in various regions of the world, as well as the synergistic effect of cigarette smoking and the effect in never-smokers [8][9][10]73,[77][78][79][80][81] as well as analyzing the histological types of lung cancer [82].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%